A variance ratio test of random walk in the stock exchange of Singapore - Choo, Boon Poh (2015)
This study aims to provide an insight into the behaviour of the local stock market by testing the random walk hypothesis. Random walk is an important concept which underlies the behaviour of stock prices in a weak-form efficient market. The outcome of such a test has several significant implications. These include the applicability of many well-known asset pricing models and stock price charting techniques to the Singapore stock market. Although many local studies have been conducted on this topic, this study differs from the rest by employing the variance ratio test developed only recently by Andrew Lo and Craig MacK.inlay in 1988. This test was performed on a data set which consisted of 6 local stock indices and stock prices of 8 companies, spanning a 5-year period from 1988 to 1992. The results of the tests on indices generally indicate that the local market is efficient in the weak form, although some sector-specific long run departures from randomness are also observed. Results of the tests on individual stocks also appear to support this claim of weak-form efficiency.